Hepatorenal syndrome in association with alcoholic hepatitis and Zieve’s syndrome - Carrasco, Luis (2022)
Alcoholic liver disease has a broad spectrum of diseases, including alcoholic hepatitis, which in its severe forms can lead to hepatorenal syndrome. Anemia is common in alcoholic patients, but a hemolytic anemia in association with hyperlipidemia and jaundice is recognized as Zieve’s syndrome. A 42 year old man with heavy alcohol consumption was admitted for jaundice and abdominal pain. During his evolution, he presented progressive azotemia and hemolytic anemia. The diagnosis of hepatorenal syndrome associated with alcoholic hepatitis was made, as well as a Zieve’s syndrome. He was treated with corticosteroid therapy and the combination of albumin and norepinephrine, in addition to alcohol withdrawal, with favorable results.